An Integrated Collaboration Framework for Sustainable Sugar Supply Chains - Wike Agustin Prima Dania; Ke Xing; Yousef Amer (International Journal of Supply Chain Management, 2019)
Stakeholders in sugar supply chains face challenges to identify strengths and weaknesses, as well as opportunities and capabilities of all collaborating stakeholders. This paper proposes a conceptual model as a framework for sustainable sugar supply chains to achieve an effective collaboration system. This model identifies essential elements and how they are linked in the boundary of sustainability. An existing general collaboration model is selected as the basis to develop a new supply chain collaboration model based on the characteristics, the synergies, and the elements. The framework consisting of six elements: boundary and context; drivers (value proposition, assets, and supply chain capabilities); stakeholder requirements; collaboration system requirements; quality indicators; and a common goal. This conceptual model gives insight to the sugar stakeholders who join in collaboration regarding what are the specific drivers and elements that possible and essential to propose a sustainable collaboration, what their roles are, and how they are linked. The finding can be used as the basis for a collaboration quality assessment model.